Investigating brain metabolite levels in adolescents living with HIV using atlas-based magnetic resonance spectroscopic imaging (MRSI) - Maharaj, Sonam (Department of Human Biology, 2025)
Deficiencies in brain function and structure have been linked to perinatally acquired HIV (PHIV) despite the introduction of antiretroviral therapy (ART). Current studies are predominantly based on single voxel magnetic resonance spectroscopy (MRS) in younger children, with inconsistent findings. We aimed to develop atlas-based pipelines for analysing MRSI data to examine whether there are differences in brain metabolite levels between adolescents with PHIV and uninfected controls. The study participants were 165 adolescents, of whom 86 were adolescents living with HIV from the CHER trial and 79 were age- and sociodemographically- matched uninfected controls. They were scanned on a Siemens 3T Skyra scanner with the scanning protocol including a high-resolution T1- weighted structural MRI using a multi-echo magnetization-prepared rapid acquisition gradient echo (MEMPRAGE) sequence and volumetric MRSI using spiral-encoded localized adiabatic selective refocusing (LASER) CSI. LCModel was utilized to achieve spec